2021
DOI: 10.1177/23982128211011923
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hippocampal-dependent task performance and hippocampal grey matter myelination and iron content

Abstract: Individual differences in scene imagination, autobiographical memory recall, future thinking and spatial navigation have long been linked with hippocampal structure in healthy people, although evidence for such relationships is, in fact, mixed. Extant studies have predominantly concentrated on hippocampal volume. However, it is now possible to use quantitative neuroimaging techniques to model different properties of tissue microstructure in vivo such as myelination and iron. Previous work has linked such measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…These results offer a new perspective on individual differences in autobiographical memory recall ability. This is especially welcome given the current lack of a clear biological explanation for such variations in the healthy population ( Clark et al, 2020 ; Clark et al, 2021a ; LePort et al, 2012 ; Maguire et al, 2003 ; Palombo et al, 2018 ; Van Petten, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results offer a new perspective on individual differences in autobiographical memory recall ability. This is especially welcome given the current lack of a clear biological explanation for such variations in the healthy population ( Clark et al, 2020 ; Clark et al, 2021a ; LePort et al, 2012 ; Maguire et al, 2003 ; Palombo et al, 2018 ; Van Petten, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that the hippocampus is central to the processing of autobiographical memories, and hippocampal damage is linked with autobiographical memory impairments ( McCormick et al, 2018 ; Scoville and Milner, 1957 ; Winocur and Moscovitch, 2011 ). However, no consistent relationship between autobiographical memory recall ability and hippocampal grey matter volume or microstructure has been identified in healthy individuals ( Clark et al, 2020 ; Clark et al, 2021a ; LePort et al, 2012 ; Maguire et al, 2003 ; Van Petten, 2004 ). The hippocampus does not act alone, and functional neuroimaging studies have revealed that a distributed set of brain areas supports autobiographical memory recall along with the hippocampus, including the parahippocampal, retrosplenial, parietal and medial prefrontal cortices ( Andrews-Hanna et al, 2014 ; Maguire, 2001 ; Spreng et al, 2009 ; Svoboda et al, 2006 ).…”
Section: Introductionmentioning
confidence: 97%
“…The higher cardiorespiratory fitness and physical activity in aged subjects, have been found to be associated with greater brain structures integrity, and better memory performance (Burzynska et al, 2015). Previous studies confirmed that, exercise training increases gray matter integrity in brain, and volume of brain regions, particularly entorhinal cortex and hippocampus in both human and animal studies (Voss et al, 2013;Ten Brinke et al, 2015;Chieffi et al, 2017;Firth et al, 2018;Tsai S.-F. et al, 2018;Clark et al, 2021), and also, brain white matter of memoryrelated regions in people with mild cognitive impairment (Amjad et al, 2019). In addition, reduced hippocampal atrophy together with improved memory were reported following 6-12 weeks of exercise training in early stage of Alzheimer's disease with this finding (Chirles et al, 2017;Ma et al, 2017;Morris et al, 2017).…”
Section: Neurogenesismentioning
confidence: 92%
“…These results offer a new perspective on the neural instantiation of autobiographical memories, and in particular on drivers of individual differences in recall ability. This is especially welcome given the dearth of consistent findings linking hippocampal grey matter volume or microstructure with autobiographical memory recall ability in the healthy population (Clark et al, 2020;Clark et al, 2021a;LePort et al, 2012;Maguire et al, 2003;Van Petten, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that the hippocampus is central to the processing of autobiographical memories, and hippocampal damage is linked with autobiographical memory impairments (McCormick et al, 2018;Scoville and Milner, 1957;Winocur and Moscovitch, 2011). However, no consistent relationship between autobiographical memory recall ability and hippocampal grey matter volume or microstructure has been identified in healthy individuals (Clark et al, 2020;Clark et al, 2021a;LePort et al, 2012;Maguire et al, 2003;Van Petten, 2004). The hippocampus does not act alone, and functional neuroimaging studies have revealed that a distributed set of brain areas supports autobiographical memory recall along with the hippocampus, including the parahippocampal, retrosplenial, parietal and medial prefrontal cortices (Andrews-Hanna et al, 2014;Maguire, 2001;Spreng et al, 2009;Svoboda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%